Correlating Structural and Functional Damage in Glaucoma. Issue 12 (December 2019) - Torres, Lucas A.; Hatanaka, Marcelo
Abstract : Structural and functional tests are essential for detecting and monitoring glaucomatous damage. However, the correlations between structural and functional tests in glaucoma are complex and faulty, with the combination of both modalities being recommended for better assessment of glaucoma. The objective of this review is to explore investigations from the last 5 years in the field of structure-function correlation in glaucoma that contributed to increment in the understanding of this correlation and have the potential to improve the diagnosis and detection of glaucoma progression.